Self Hipnosis terhadap mual muntah kehamilan trimester I - Nur Djanah; Ana Kurniati (Poltekkes Kemenkes Yogyakarta, 2015)
Nausea and vomiting in pregnancy is a common problem, which can be serious for both mother and baby. More than half (50-90%) of pregnant women experiencing nausea vomiting. Numerous attempts have been made to reduce the nausea vomiting with pharmacological and non-pharmacological approaches. Self hypnosls is one of the non-pharmacological approach to reduce the symptoms of nausea and vomiting. The purpose of this research was to describes the effect of self hypnosis to decrease the frequency of nausea vomiting of first trimester pregnancy.The design used was quasi experiment with the approach -of One Group pretest-postest against 30 pregnant women trimester I use consecutive sampling corresponding to the criteria of inclusion and exclusion.Self hypnosis was done every 10-15 minutes for three days. Data collection of pretest and posttest using the measuing instrument PUQE-74 (Pregnancy-Unique Quantification of Emesss), data analysis using the Wilcoxon Rank Test. There are significant differences on decreases of the score nausea (0.007), score vomiting retching (0,013), and score of nausea vomiting (0.002) before and after the intervention. The conclusion was that the self hypnosis can decreases of the frequency of nauseavomiting of pregnancy. Self hypnosls can be applied as a non-pharmacological therapy to decrease frequency of nausea vomiting of first trimester pregnancy.